FACTORS AFFECTING ZAKAT PAYMENT THROUGH INSTITUTION OF AMIL: MUZAKKI’S PERSPECTIVES ANALYSIS - Ayuniyyah, Qurroh (Al-Infaq: Jurnal Ekonomi Islam, 2011)
As the third pillar of Islam, zakat has an important role from both social and economic perspectives. Socially, zakat can build brotherhood and sense of belonging among Muslims. Beside purifies the wealth, zakat also can reduce the social gap between the have and the have not. Zakat empirically can alleviate the poverty as well as generate prosperity of the ummah which was realized during the Golden Age of Umar bin Abdul Azis Caliph. At that period, zakat was controlled, collected, and disbursed by trustable and professional amil officers. In Indonesia, the potential of zakat is promising. This condition is indicated by reaching 3.4 percent of Gross Domestic Product (GDP) that equals to 217 trillion Rupiahs (BAZNAS and FEM, 2011). Unfortunately, the realization of the zakat collection is still far behind its potential. In 2010, zakat collection was only 1.5 trillion Rupiahs or less than 1 percent from the expectation. This fact shows that the awareness to pay zakat through institutions in Indonesia is still poor. Therefore, this paper attempts to analyze the factors that determine muzakki to pay zakat through the Institutions by taking case study of Badan Amil Zakat Nasional (BAZNAS), as the National Zakat Board in Indonesia. One hundred respondents from zakat payers through BAZNAS and one hundred respondents from non-institution zakat payers have been selected as the sample of the research. The respondents have been deeply interviewed on December 2009 to February 2010. The samples were determined using purposive convenience sampling (non probability sampling). Descriptive statistics, IPA (Importance Performance Analysis) and CSI (Customer Satisfaction Index) methods have been used as analytical methods.